The Visual Identity of Brands and its Impact on the Visual Perception of the Saudi Public: A Field Study on Multinational Automotive Companies - Aljahli, Abdulrahman bin Ibrahim (Journal of Posthumanism, 2025)
This study investigates the impact of the visual identity of multinational automotive companies' websites on the visual perception of car owners in the Kingdom of Saudi Arabia. The primary objective is to understand how exposure to the visual elements on these websites such as logos, colors, and graphics affects consumer preferences and their overall perception of automotive brands. The study’s population consists of car owners who have interacted with the websites of multinational automotive companies, and the sample includes 400 respondents from various regions of Saudi Arabia. The research employs a descriptive approach using the survey method to collect data through an electronic questionnaire. The findings indicate that a significant percentage of respondents are frequently exposed to these websites, with 52.8% reporting regular visits. The study also reveals that Toyota, Mercedes, and Chevrolet are the most preferred brands based on website exposure. Additionally, visual identity elements such as logos and colors play a vital role in shaping consumer perceptions and are seen as highly influential in promoting the brand. Results also show that 64% of participants believe that the visual identity of these websites significantly contributes to the promotion of automotive brands. Furthermore, the study emphasizes that visual identity elements complement the content of the websites, reinforcing the importance of high-quality information in engaging users. Based on the findings, the study recommends the development of educational projects for students in Public Relations and Advertising to enhance their understanding of visual identity's role in consumer behavior. It also advises automotive companies to prioritize specialized advertising departments to ensure effective integration of design and editorial elements. Lastly, the research underscores the need for a balance between modern design trends and traditional cultural values in creating brand identities. This study provides valuable insights into the strategic use of visual identity for automotive companies and offers practical recommendations for optimizing website design to boost brand recognition and consumer engagement.